Colors of veracity : a quest for truth in China, and beyond - Schwarcz, Vera, 1947- (University of Hawaiʻi Press, 2014)
In Colors of Veracity, Vera Schwarcz condenses four decades of teaching and scholarship about China to raise fundamental questions about the nature of truth and history. In clear and vivid prose, she addresses contemporary moral dilemmas with a highly personal sense of ethics and aesthetics. Drawing on classical sources in Hebrew and Chinese (as well as several Greek and Japanese texts), Schwarcz brings deep and varied cultural references to bear on the question of truth and falsehood in human consciousness. An attentiveness to connotations and nuance is apparent throughout her work, which redefines both the Jewish understanding of emet (a notion of truth that encompasses authenticity) and the Chinese commitment to zhen (a vision of the real that comprises the innermost sincerity of the seeker's heart-mind). Works of art, from contemporary calligraphy and installations to fake Chinese characters and a Jewish menorah from Roman times, shed light light on the historian's task of giving voice to the dread-filled past. Following in the footsteps of literary scholar Geoffrey Hartman, Schwarcz expands on the "Philomela Project, which calls on historians to find new ways of conveying truth, especially when political authorities are bent on enforcing amnesia of past traumatic events. Truth matters, even if it cannot be mapped in its totality. Veracity is shown again and again to be neither black nor white. Schwarcz' accomplishment is a subtle depiction of "fractured luminosity," which inspires and sustains the moral conviction of those who pursue truth against all odds